Qualitative research topics in language teacher education - Barkhuizen, Gary Patrick (Routledge, 2019)
"Many students and novice researchers may have a general idea of a topic they would like to research, but have a difficult time settling on a more specific topic and associated research questions. Addressing this problem, this book features contributions from over thirty diverse and experienced research supervisors, mentors, and principle investigators in the field of language teacher education. The chapters are autobiographic in nature, with each contributing author reflecting on relevant, current and innovative research topics through the lens of their own professional life and research work. Offering explicit research topics and strategies for each area of expertise, this book will serve as a useful reference for the seasoned qualitative or narrative research practitioner, and a helpful guide for the new researcher narrowing down their own research topics"--